Экспрессивность как историческая категория 成语; Молодой ученый; № 9 (89) - Яковлева Е. А. Екатерина Александровна; Селина А. В. Анна Вячеславовна; Болсуновская Л. М. Людмила Михайловна; Хоречко У. В. Ульяна Викторовна (Филология, 2015)
Заглавие с экрана